Covid-19 sürecinde katılım bankaları ile özel mevduat bankalarının performans değerlendirmesi: Türkiye örneği - DAĞIDIR ÇAKAN, CANAN (My University, 2022)
Bu çalışmada amaç COVİD-19 öncesi dönem ile pandeminin devam ettiği 2020 ve 2021 verileri aracılığıyla katılım bankaları ile mevduat bankalarının bu durumdan etkilenme düzeyinin farklı olup olmadığının ortaya konmasıdır. Bu kapsamda örneklem olarak seçilmiş beş özel mevduat bankası ile beş katılım bankası karlılık, risk ve borç ödeme gücü, likidite, aktif kalitesi ve sermaye yeterliliği bakımından oran analizi yöntemi ile değerlendirilmiştir. Katılım bankaları ile mevduat bankaları arasındaki oransal farklılıkların istatistiksel olarak anlamlı olup olmadığı ise t-testi ile sınanmıştır. Elde edilen sonuçlara göre pandemi sürecinde aktif kalitesi bakımından katılım bankalarının daha verimli olduğu, bunun haricindeki değişkenlerde anlamlı bir farklılık olmadığı sonucuna ulaşılmıştır.

This study aims to reveal whether the level of exposure of participation banks and deposit banks is different from the period before COVID-19 and 2020 and 2021 when the pandemic continues. In this context, five private deposit banks and five participating banks selected as samples were evaluated with the ratio analysis method of profitability, risk and solvency, liquidity, asset quality, and capital adequacy. Whether the proportional differences between participation banks and deposit banks are statistically significant was tested with the t-test. According to the results obtained, it was concluded that participation banks were more efficient in terms of asset quality during the pandemic process, and there was no significant difference in other variables.
Performance evaluation of participation banks and private deposit banks in the covid-19 process: The case of Turkey
Keywords: COVİD-19; KATILIM BANKALARI; MEVDUAT BANKALARI; ORAN ANALİZİ; T-TESTİ; This study aims to reveal whether the level of exposure of participation banks and deposit banks is different from the period before COVID-19 and 2020 and 2021 when the pandemic continues. In this context; five private deposit banks and five participating banks selected as samples were evaluated with the ratio analysis method of profitability; risk and solvency; liquidity; asset quality; and capital adequacy. Whether the proportional differences between participation banks and deposit banks are statistically significant was tested with the t-test. According to the results obtained; it was concluded that participation banks were more efficient in terms of asset quality during the pandemic process; COVID-19; PARTICIPATION BANKS; DEPOSIT BANKS; RATIO ANALYSIS; T-TEST.